ORGANIZATIONAL COMMITMENT AS A DETERMINING FACTOR OF TEACHERS' ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN ISLAMIC EDUCATIONAL INSTITUTIONS; META-ANALYSIS - Dede Ridho Firdaus; Anis Zohriah; Rijal Firdaos (LP2M IAIN Sultan Amai Gorontalo, 2024)
This research aims to draw comprehensive conclusions from the results of relevant previous research. Seeing the strength of the correlation between organizational commitment and organizational citizenship behavior of teachers in Islamic educational institutions. Using Meta-Analysis research and systematic reviews using JASP 0.18.1.0 software. The data found were 25 articles through searches on Google Scholar and Mendeley search with the keywords Organizational commitment, organization citizenship behavior teacher. 10 articles were selected based on predetermined researcher characteristics and criteria. The data taken from the selected articles is the number of samples (N) and the r value for each article, then the effect size is analyzed. Includes; Madrasah Ibtidaiyah, Madrasah Tsanawiyah, Madarasah Aliyah Data from research on organizational commitment to organizational citizenship behavior of teachers at Islamic educational institutions were analyzed in depth to find out how big the correlation between organizational commitment is to organizational citizenship behavior of teachers at Islamic educational institutions. This research begins with formulating the research topic, tracing research results that are relevant for analysis. This can be seen from the research results which show that the results of analysis using the random effect model show that there is a significant positive correlation between organizational commitment and teacher organizational citizenship behavior. The strength of the correlation between organizational commitment and teacher organizational citizenship behavior is included in the low significance category1 (re: 0.790).